CCNA security 640-554 official cert guide / Learn, prepare and practice for exam success - Barker, Keith; Morris, Scott; Cisco Networking Academy Program (2013)
These self-study resources are built with the objective of providing assessment, review, and practice to help ensure you are fully prepared for your certification exam. This guide presents you with an organized test preparation routine through the use of proven series elements and techniques.
Includes index.
oif 23/06/15
Loan
Keywords: Computer networks; Computer networks; Electronic data processing personnel; Telecommunications engineers